The dark side of belief in Covid-19 scientists and scientific evidence. (July 2022) - Graso, Maja; Henwood, Amanda; Aquino, Karl; Dolan, Paul; Chen, Fan Xuan
Abstract: We draw from an interdisciplinary literature on convictions to examine the manifestations and consequences of firmly held beliefs in Covid-19 (C19) science. Across three studies ( N = 743), we assess participants' beliefs in C19 experts, and beliefs in supported and unsupported empirical evidence. Study 1 establishes the basic theoretical links and we show that an individual's belief in science on C19 is associated with dispositional belief in science and moralization of C19 mitigation measures. Our subsequent two studies show how stronger belief in C19 science influences distrust in unmasked individuals past the mandates, and greater endorsement of pandemic mitigation authoritarianism. We document the dark side that emerges when belief in C19 science extends beyond the generally desirable scientific literacy and manifests as a conviction that public health experts are the only ones who can handle the pandemic, and that even unsupported claims about C19 are supported by scientific evidence (e.g., risk of outdoor transmission is high). We also highlight our political ideology findings showing that both liberals and conservatives mis-calibrate C19 risks in different ways, and we conclude with discussing how examining the darker side of scientific beliefs can inform our understanding of people's reactions to the pandemic. Highlights: We reinforce past research showing that beliefs in C19 science impact behavior. Stronger beliefs increase compliance and reduce trust in conspiracy theories. When beliefs in C19 science become convictions, social trust and cohesion may suffer. Convictions manifest as beliefs that unfounded claims are supported with science. Liberals over- and conservatives under-attribute claims to scientific evidence.